Pengembangan Buku Ajar Berbasis Kearifan Lokal Ritual Helketa untuk Meningkatkan Hasil Belajar Pendidikan Pancasila pada Materi Keberagaman Budaya Siswa Kelas IV Sekolah Dasar - Betty, Ingrit; Koli, Radka Bodkova; Nahak, Roswita Lioba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop a textbook based on the local wisdom of the Helketa Ritual to improve fourth-grade elementary school students' learning outcomes in Pancasila Education, particularly on cultural diversity materials. The development of contextual teaching materials is essential to bridge conceptual understanding with students' socio-cultural experiences while preserving local cultural values in the learning process. This research employed the Research and Development (R&D) method using the Four-D (4D) model, comprising the stages of define, design, develop, and disseminate. The study was conducted at SD Inpres Supul Meo, involving material, language, and media experts, teachers, and fourth-grade students. Data were collected through validation sheets, practicality questionnaires, and learning outcome tests (pretest and posttest) and analyzed using descriptive statistics and N-Gain analysis. The findings revealed that the developed textbook met the criteria of being highly valid, practical, and effective. Material validation achieved 82.03%, language validation 84.09%, and media validation 87.50%, all categorized as highly valid. The practicality assessment demonstrated that both students and teachers perceived the textbook as highly practical for classroom implementation. Furthermore, students' mean scores increased significantly from 48.87 in the pretest to 91.00 in the posttest, with an average N-Gain score of 0.8283 (82.83%), indicating a high level of effectiveness. These findings suggest that integrating Helketa Ritual values into Pancasila Education textbooks provides meaningful and contextual learning experiences while improving students' learning outcomes and promoting the preservation of local cultural wisdom in elementary education.